ANALISIS DAMPAK MEA TERHADAP TOTAL EKSPOR DAN TOTAL IMPOR INDONESIA - Borromeu, Jezzuvo; Setiawina, Nyoman Djinar (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2020)
The purpose of this study is to analyze trends in total exports and imports of Indonesia after AEC in 2019-2023 and to analyze the significant differences in total exports and imports of Indonesia after and before AEC. This study uses secondary data obtained from the Central Statistics Agency and World Development Indicators. The technique used for analysis this study is trend analysis to determine the trend of total exports and imports for the next 5 years and simple linear regression to determine the effect of the AEC on Indonesia's total exports and imports. The results of this study indicate that the trend of total exports and total imports of Indonesia increases every year after the AEC in 2019-2023, there are significant differences in total exports and total imports of Indonesia after and before AEC.